Victor and Constance Daniel and Emancipatory Education at the Cardinal Gibbons Institute - Moore, Cecilia A. (Catholic Education: A Journal of Inquiry and Practice, 2001)
From 1924 to 1934, Victor and Constance Daniel practiced emancipatory education at the Cardinal Gibbons Institute, a Catholic high school for African Americans in Ridge, Maryland. The purpose of emancipatory education was to liberate Black and White Americans, both mentally and morally, from the vestiges of slavery that created and perpetuated racism in the United States. Emancipatory education placed the study and appreciation of African American history and culture at its center. The Daniels rooted their development of emancipatory education in their experience as Catholic educators, the racial uplift movement of the late 19th and early 20th centuries, and African American scholarship.